Effects of Y addition on the microstructure and properties of Cu-Cr-Zr alloy during the directional solidification process. (5th September 2018) - Zhu, Dongsheng; Peng, Minghu; Zhong, Yunbo; Shen, Zhe; Zheng, Tianxiang; Wang, Huai; Ren, Weili; Wang, Jiang; Li, Chuanjun; Ren, Zhongming
Abstract: The effects of Y addition on the solidified microstructure, mechanical and electrical properties of Cu-1Cr-0.1Zr- x Y ( x  = 0–0.1 wt%) alloys were investigated during the directional solidification process. The results show that the Cu-rich structures are the long cellular when the additions of Y are 0.02 wt% and 0.04 wt%. They are the short cellular when the addition of Y lower than 0.02 wt% and exceed 0.04 wt%. After the heat treatment process, the size of the coarse Cr phase changes from 500 nm (without Y) to 200 nm (0.06 wt%Y), and the dispersed Cr-rich precipitates become more with the addition of 0.06 wt% Y, which accounts for the increase in tensile strength and electrical conductivity of Cu-Cr-Zr-Y alloy. The Cu-1Cr-0.1Zr-0.06Y alloy possesses the best ultimate tensile strength (UTS), elongation and electrical conductivity which are 254.1 MPa, 48% and 84.59% IACS, respectively.